The effects of detraining on the technical parameters in young table tennis players - Katsikadelis, M.; Pilianidis, T.; Mantzouranis, N.; Agelousis, N. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
Technique is one of the most important factors which define the match performance of Table Tennis players. The aim of the present study was to evaluate the effects of a 20-day detraining period on the technical parameters in young Table Tennis players. Twenty five (n=25) athletes (15 boys & 10 girls), aged 12±1.8yrs with body mass of 45.9±12.9 kg and stature 1.52±0.1cm participated in the current study. All athletes were right-handed and they were considered as advanced players, having 5 training sessions per week and they performed an in season 10-week Multiball Table Tennis specific protocol. The Table Tennis Specific Test Battery (TTSTB) with the balls launch rate at 80balls/min was applied in order to identify the effects of lack of training on the technical modelling of the Table Tennis players. The technical parameters which were recorded in the study subjects were: Reaction Speed 1, 2 (RS), Displacement Speed 1, 2, 3 (DS), Skill Speed 1, 2 (SS) and Ocular Manual co-ordination (OCM) and they were applied pre-and-post the 20-day detraining period. A t test was used to identify the differences in the playing parameters from the initial to final technical evaluation of the TTSTB. Spearman`s (ñ) analysis was applied in order to determine whether the testing parameters were significantly correlated. All statistical analyses were carried out with the IBM-SPSS 21.0 for Windows. The results showed that the mean scores of Displacement Speed 1 [t (1, 24) = 2.32, p=0.29] and Displacement Speed 3 [t (1, 24) = -3.01, p=0.06] were significantly decreased after the 20-day detraining. In the amount of the studied subjects, all the mean scores of the TTSTB during the final technical evaluation were recorded lower than the initial but without any significant differences in the technical efficiency of the players. The total scores in the Reaction Speed 1 recorded 9.7±3 successful shots, while the Displacement Speed 3 recorded 10.2±3.4 accurate shots. Spearman`s (ñ) correlation analysis reported a statistically significant negative correlation between the DS3 and SS1, (ñ= 0.53, DF=25, p<0.01) and a significant interaction between DS3 and OCM, (ñ=0.64, DF=25, p<0.01). In conclusion, the better the playing technique is learned by applying the Multiball training method, the longer it will be retained in the developmental age Table Tennis players, even after a 20-day detraining period. However, it should be noted that the above findings mainly regard the technical improvement of the players in the training rather than the evaluation of a match in Table Tennis.